REVERSED TRANSFER OF ARGUMENT-COUNTERARGUMENT STRUCTURE IN INDONESIAN EFL LEARNERS’ L1 AND L2 ARGUMENTATIVE WRITING - Rusfandi, Rusfandi (LLT Journal: A Journal on Language and Language Teaching, 2025)
The influence of L2 writing on L1 writing has been viewed as a complex process. Bilinguals are often faced with challenges in trying to reuse prior writing knowledge received through L2 and in trying to reshape that writing knowledge when composing in L1. This study aims to gain evidence of a reversed transfer of writing knowledge from L2 to L1 in an Indonesian EFL teaching context. This quantitative research analyzed EFL learners' L2 and L1 essays after an L2 writing instruction which focuses on argumentative writing had been provided for one semester in an Indonesian university. The study found evidence of a reversed transfer of argument-counterargument structure from L2 English to L1 Indonesian among third-year English majors. However, this transfer process is dynamic because it depends on mediating factors, including the L2 learners’ different levels of understanding of the argument-counterargument structure, L2 proficiency, and perceived audience expectation in a specific language. There was also a significant correlation in the overall scores between the L2 and L1 essays produced by the English majors. The findings suggest that conceptual knowledge of writing is transferable across languages, and developing L2 writing ability could directly/indirectly trigger L2 learners’ L1 writing development.